Is the role of probiotics friendly in the treatment of periodontal diseases !! - Deepa D; Mehta D (Wolters Kluwer Medknow Publications, 2009)
Probiotics utilize naturally occurring bacteria to confer a health benefit when administered in adequate amounts. A few conventional foods containing probiotics are yogurt, fermented and unfermented milk, soy beverages etc. Most often, they come from two groups of bacteria, Lactobacillus or Bifidobacterium. Probiotics have been extensively studied for their health promoting effects. Scientific understanding of probiotics and their potential for preventing and treating periodontal conditions is at its infancy, but moving ahead. Extensive research to create a probiotic product intended to maintain dental and periodontal health is needed.